PENERAPAN ASAS KESEIMBANGAN DALAM PERJANJIAN KREDIT RUMAH - Windi Arista (Justici, 2022)
Home is a basic need of every human being. The house has a very important function for humans, namely as a shelter from all weather and as a place to build a family and as a place to carry out various business activities. In order to accommodate the community's need to own a house, the banking sector offers a Home Ownership Credit facility, which in this discussion will be abbreviated as KPR. KPR is a credit facility provided by banks to individual customers who will buy or repair a house. At the implementation stage of the implementation of the KPR Agreement, there may be "certain circumstances" that are not as usual, causing the balance of benefits from the agreement to not be achieved.